Komunikasi dan Pemberdayaan: Strategi Komunitas WEPOSE Surabaya dalam Memberdayakan Anak Marginal - Fikrin Najib; Dyva Claretta (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to explore the communication strategy implemented by the WEPOSE Community in Surabaya for empowering marginalized children. The analysis refers to Hafied Cangara’s five stages of communication strategy which include research, plan, execute, measure, and report. The research adopts a descriptive qualitative approach with data collected through in-depth interviews with community organizers. The findings indicate that WEPOSE applies a systematic communication strategy supported by participatory and dialogic communication approaches that actively involve children and the surrounding community in every stage of the program. The empowerment initiatives include educational activities such as regular learning sessions and social programs like parenting support, youth training, free health check-ups, educational tours, and social campaigns. This strategy has proven effective in enhancing children's knowledge, character, and social participation. The study recommends strengthening participatory communication as a key foundation for successful empowerment programs.